LEFT GOVERNMENTS IN POWER: Cuba 60 years of revolution, 60 years of standing firm against imperialism. (July 2019) - Miller, Rob
Abstract : This year marks the sixtieth anniversary of the Cuban Revolution. Despite ever-present threats and aggressions from the world's largest superpower, just seventy miles away, the Cuban Revolution has survived and developed over time. Cuban achievements in education and health have been remarkable and so have Cuban expressions of international solidarity in practice. There is so much to celebrate. But the need for solidarity against the US blockade continues, supporting the Cuban people in their right to independence, building a better world for all.